Perancangan Aplikasi Pelaporan Surveilans Mortality di Kabupaten Barru - Muhriati, Muhriati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Mortality surveillance is an activity of collecting, processing, analysing, and interpreting data about deaths. The purpose of mortality surveillance is to monitor death events on an ongoing basis and determine risk factors and or underlying causes of death cases in the Barru district area as material for policy making by the government, effective implementation in 2020 by involving all health centres in Barru district, and hospitals in 2021. Mortality surveillance reporting has not been integrated between puskesmas, hospitals and district offices, resulting in data not being available in real time and the possibility of data duplication. In overcoming this challenge, technological developments and the presence of an integrated application can be a very relevant solution. Requirement stage of mortality surveillance reporting system design starts from the stage of making use cases, data flow diagrams, to the user interface stage. The evaluation stage to measure user experience involved 20 respondents using the UEQ method. The measurement results show that the mortality surveillance reporting application can fulfil user expectations